THE EFFECTIVENESS OF TASK-BASED TEACHING AND LEARNING (TBTL) IN MODERN EDUCATION - Xalilova Mohichehra; Abdullayeva Ruxsora (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Task-Based Teaching and Learning (TBTL) has emerged as a cornerstone of modern pedagogical methodology, shifting the educational focus from traditional, teacher-centered rote learning to a more dynamic, student-centric approach. This article explores the theoretical foundations and practical applications of TBTL, emphasizing its role in developing communicative competence and real-world problem-solving skills. The core objective of TBTL is to engage learners in meaningful tasks where language or knowledge is used as a tool to achieve a specific outcome rather than as an isolated subject of study. By analyzing the structural framework of TBTL—comprising pre-task, task cycle, and post-task phases—this study highlights how the method fosters learner autonomy and motivation. Furthermore, the article discusses the benefits of TBTL in enhancing social interaction and critical thinking, while also addressing common challenges such as time constraints and assessment complexities in large classrooms. Through practical examples in English language teaching and other disciplines like history and mathematics, the research demonstrates that TBTL prepares students for real-life challenges by bridging the gap between theoretical classroom knowledge and practical application. Unlike traditional methods that prioritize grammatical accuracy through rote memorization, TBTL focuses on the completion of meaningful tasks as the primary unit of instruction. The study examines the impact on student motivation, autonomy, and the development of practical communicative competence. Ultimately, the study concludes that the integration of TBTL into the curriculum is essential for developing active, independent, and creative individuals capable of thriving in a globalized society. The findings suggest that a holistic approach, integrating cognitive development with social awareness, is essential for fostering genuine communicative autonomy in diverse linguistic contexts.